Magneto-Sensitive Rubber in a Vehicle Application Context – Exploring the Potential - Wang, Bochao; Hu, Tao; Shen, Longjiang; Li, Jun; Xu, Zhenbang; Kari, Leif; Gong, Xinglong (Frontiers in Materials, 2021)
The application of magneto-sensitive (MS) rubber in a vehicle vibration control area is likely to be expected. This conclusion is based on the following two reasons: the maturity of fabrication of MS rubber which meets the application requirement and the feasibility of constitutive model of MS rubber that accurately reflects its mechanical performance. Compared with the traditional rubber, small ferromagnetic particles are embedded in the elastomer of MS rubber leading to a change of mechanical properties when an external magnetic field is applied. Therefore, devices with MS rubber can be viewed as a semi-active actuator. In this work, MS rubber with a relative high increase in magneto-induced modulus is fabricated and characterized. Furthermore, a one dimensional constitutive model to depict the magnetic, frequency and strain amplitude dependent dynamic modulus of MS rubber is applied. Finally, simulations of a MS rubber semi-active suspension under a bump and a random ground excitation with different control strategies on a quarter vehicle model are conducted to illustrate the feasibility of the MS rubber in the vehicle vibration control application context.